Assessing service usage and protective factors in a pediatric psychiatry clinic during the COVID-19 pandemic - Caruso, A. J.; Basu, A.; Urban, T. H.; Kaskas, M. M.; Rotter, N.; Wozniak, J.; Friedman, D. (Frontiers in Psychology, 2024)
Youth with developmental and pre-existing mental health conditions have been particularly vulnerable to declines in psychological functioning during the COVID-19 pandemic. This study aimed to first, analyze service usage within an outpatient child and adolescent psychiatry clinic in the months preceding and during the COVID-19 pandemic, and second, to examine associations with potential protective factors against mental health concerns in a treatment-engaged sample. Service usage was examined using clinic billing data, and reports on protective factors were gathered via parent survey of 81 children ages 6-17 years who received mental health treatment in an outpatient psychiatry clinic during the pandemic. Protective factors were assessed at the individual, family, and community levels, and included children's use of coping strategies, parental resilience, and parents' perceived social supports. Study outcomes, including mental health concerns, mental health emergencies, pandemic-related distress, and social impact of the pandemic, were analyzed via Pearson correlations and simultaneous multiple linear regressions. Findings suggest increased service usage and child coping, parental resilience, and social connectedness as factors associated with fewer mental health concerns in youth with psychiatric concerns during the pandemic. This study lends support for expanding psychiatric services with continued use of telemedicine platforms. Further, findings suggest a mental health benefit to optimizing individual, parental, and community-based resources to enhance children's psychological functioning, particularly for youth with pre-existing mental health conditions.